Pengembangan Media Digital Book Bergambar Seri Berbasis Examples Non Examples untuk Meningkatkan Keterampilan Menulis Karangan Narasi Siswa - Maryam Maryam; Rasiman Rasiman; Ida Dwijayanti (Jurnal Kualita Pendidikan, 2022)
This research is motivated by the low skills of writing narrative essays for fifth grade students of SDN Sidalang 01 based on observations and interviews with classroom teachers. This research aims to produce digital media illustrated book series based on examples non examples to improve the skills of writing narrative essays. The type of research used is Thiagarajan Semmel and Semmel 4-D (Four-D) development research. The data collection method used is the method of observation, questionnaires and tests. The results of the research at the definition and design stages produced a digital media design for a series of picture books which in its presentation used the examples non examples syntax. Then the development stage was carried out, namely by expert validation, practicality testing and effectiveness testing on digital media based on examples-non-examples-based picture books. The results of the media expert validity test got an average score of 89.37% with very good criteria and 89.5% according to material experts with very good criteria. The results of the practicality test based on student responses got an average score of 92% and 90.7% based on the teacher's response with very good criteria. The effectiveness of digital media illustrated book series based on examples non examples tested valid based on the t test got a sig (2-tailed) of 0.000 so that Ho was rejected, while the average N-Gain result was 0.57 in the moderate improvement category. It can be concluded that the digital media picture book series based on examples and non-examples is proven to be valid and feasible to use in learning.